Introduction to data mining - Tan, Pang-Ning (Pearson Addison Wesley, 2006)
Introduction to Data Mining is a complete introduction to data mining for students, researchers, and professionals. It provides a sound understanding of the foundations of data mining, in addition to covering many important advanced topics.